(untitled) (Journal of Guidance and Counselling Studies, 2025)
This study investigated the perception of counsellors’ behaviour on the treatment of drug-addicted clients in Minna Rehabilitation Center, Niger State. Guided by two objectives, and two null hypotheses, the study adopted a descriptive survey research design, which enabled the collection of information from both counsellors and clients without manipulating variables. The population comprised 261 respondents, consisting of 106 counsellors and 155 registered drug-addicted clients. From this, a sample size of 155 was determined using Krejcie and Morgan’s sampling table and selected through simple random sampling technique to ensure representation. Two researcher-developed instruments were used for data collection: the Perceived Influence of Counsellors’ Behaviour Questionnaire (PICBQ) and the Treatment of Drug-Addicted Clients Questionnaire (TDACQ). These measured counsellors’ behavioural attributes such as empathy, and non-judgmental attitude, along with treatment outcomes including adherence, coping ability, craving reduction, readiness to change, and relapse control. The instruments were validated by experts, yielding a strong Content Validity Index of 0.89, and reliability was confirmed with a Cronbach Alpha coefficient of 0.82 from a pilot study. Descriptive statistics were used to analyse demographic data and research questions, while Chi-square tested the hypotheses at 0.05 significance level. Findings revealed that counsellors’ interpersonal qualities greatly shaped recovery outcomes. Empathy enhanced adherence, and non-judgmental attitudes promoted openness to change. The study concluded that effective rehabilitation outcomes depend largely on counsellors’ professional conduct and interpersonal skills. It recommended regular training to enhance counsellors’ behavioural attributes, consistent ethical practice, avoidance of stigmatization, and prioritizing counsellor-client relationship quality in evaluating treatment effectiveness. It further emphasized integrating counsellors’ behavioural qualities into drug rehabilitation programmes as essential components for improving recovery outcomes.